2000
DOI: 10.1111/j.1553-2712.2000.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up Program for Emergency Department Patients with Gonorrhea or Chlamydia

Abstract: Abstract. Objectives: To study the performance of a centralized regional follow-up program organized by a municipal department of health (DH) for female patients presenting to the emergency department (ED) with Neisseria gonorrhoeae and/or Chlamydia trachomatis, who are not diagnosed or treated at the time of presentation. Methods: This was a retrospective observational study of female patients seen in the ED with positive cervical specimens, and their subsequent treatment and follow-up by the DH. Medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Two previous studies have shown that approximately 50% of female ED patients who ultimately test positive for NG or CT were not initially treated, often with significant delays in contacting those patients (7,8). Another study showed that only 24% of patients (both males and females) who tested positive for NG or CT were treated initially in the ED (9).…”
Section: Discussionmentioning
confidence: 94%
“…Two previous studies have shown that approximately 50% of female ED patients who ultimately test positive for NG or CT were not initially treated, often with significant delays in contacting those patients (7,8). Another study showed that only 24% of patients (both males and females) who tested positive for NG or CT were treated initially in the ED (9).…”
Section: Discussionmentioning
confidence: 94%
“…11,12 However, others have emphasized the importance of systematic and efficient follow-up with positive results of all female patients after ED release. 5,13 Recently, we showed that we can improve our ability to contact women with their STI test results, and reduced our lost to follow-up rate from 40% to 24%. 3 Thus, timely followup of positive STI results is a necessary public health intervention for adolescent women utilizing the ED.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies demonstrate improved quality of care is possible, including proper follow-up and compliance with CDC treatment guidelines through implementation of specific system changes and actions [29••], and successful partnership with health departments [27]. Specific recommendations to improve ED STI diagnosis and management are summarized in Table 1.…”
Section: Summary Of Emergency Department Care For Gonorrhea and Chlammentioning
confidence: 99%
“…Kelly et al [27] reviewed results of this program. Of 342 women testing positive for GC or CT, 154 (45%) were treated at the initial ED visit.…”
Section: Introductionmentioning
confidence: 97%